(untitled) (Research, Society and Development, 2022)
The objective was to analyze the hyperglycemic potential of different mango varieties at different stages of maturation. Cross-sectional, descriptive experimental research with a quantitative approach. Sample acquisition was performed at the supply center in the State of Piauí. Palmer, Rosa and Tommy Atkins mango varieties were used in two stages of ripeness, green and ripe state of ripeness. The samples were submitted to analysis procedures in quintuplicate for the content of low molecular weight sugars and moisture. Comparisons between mangoes of different varieties and maturity stages had statistically significant results (p=0.0084), when compared with ripe pink mango. The glucose determination kit proved to be effective in determining glucose than the analytical curve. The linear regression (glucose) value of 0.976 was statistically significant and developed a mathematical formula that allows estimating any concentration. There was a constant glucose/fructose relationship in different fruits, and a linear regression was created that generated a straight equation in which fructose can be estimated from the glucose value. Humidity values were not statistically significant and did not interfere with the glucose level. The tested mango varieties showed statistically significant variations in low molecular weight carbohydrate contents, especially the Rosa variety. The enzymatic method developed proved to be capable of spectrophotometrically quantifying the glucose content. It is necessary to determine the glycemic index for fruit varieties in Brazil.